Pengaruh kemampuan kerja dan motivasi kerja terhadap kinerja karyawan PT.Nusantara Card Semesta (NCS) Cabang Jambi - Aditya Rachman; Zulfina Adriani; Dwi Kurniawan (Jurnal Dinamika Manajemen, 2020)
This study aims to: determine the description of workability, work motivation, and employee performance of PT. Nusantara Card Semesta (NCS) Jambi branch. As well as to assess the effect of workability and work motivation of employees on the performance of employees of PT. Nusantara Card Semesta (NCS) Jambi Branch. Based on the study results that 1) Description of the workability of PT. Nusantara Card Semesta (NCS) Jambi branch with an average score of 106.5 is included in the very high category. The description of the average work motivation score of PT. Nusantara Card Semesta (NCS) Jambi Branch, 92.2, is included in the high class. Definition of employee performance of PT. Nusantara Card Semesta (NCS) Jambi Branch, with an average score of 99.1, is high. 2) Based on the results of multiple linear regression testing, the variables of workability and work motivation partially have a positive and significant effect on PT employees' performance. Nusantara Card Semesta (NCS) Jambi branch. Meanwhile, the variables of ability and work motivation also have a significant effect on PT employees' performance. Nusantara Card Semesta (NCS) Jambi branch.